Effect of 0.2% peracetic acid disinfection on the horizontal dimension of implant framework indexed with two autopolymerized acrylic resins - Emanuely Ronconi da Fonseca; Paula Pereira Santana; Anuar Antonio Xible; Donald A. Curtis; Stefania Carvalho Kano (SpringerOpen, 2019)
Abstract Background To minimize misfit between prosthesis and implant, the welding of the implant fixed partial denture (IFPD) framework is recommended and autopolymerized acrylic resin (AR) is the material of choice for the indexing process. As for any prosthetic device that comes into contact with saliva and blood in the oral cavity, IFPD indexed with AR must be disinfected before sending to the laboratory. However, disinfection procedures are often neglected for fear of shrinkage or distortion caused by a dimensional change of the acrylic resin. Peracetic acid is a high-level disinfectant agent at low concentrations and immersion time, with no reported toxic residues, and it is not inactivated in the presence of organic matter when compared to other disinfectants. This study aimed to evaluate the influence of 0.2% peracetic acid disinfectant solution after different storage media and times on the horizontal dimension of IFPD frameworks indexed with AR. Material and methods IFPD frameworks were indexed with two AR: group 1 Duralay and group 2 Pattern Resin LS. Each group was further divided into five subgroups according to disinfection procedure and storage medium: no disinfection and dry storage, no disinfection and water storage, 0.2% peracetic acid disinfection and water storage, 0.2% peracetic acid disinfection and peracetic acid storage, and 0.2% peracetic acid disinfection and dry storage. The horizontal dimension of the specimens and an average was established for analysis. Measurements were performed at four different storage times (hours): T0, T24, T48, T168. Results No statistical differences were found when T0 was compared to T168 for Pattern resin groups submitted to disinfection and storage in water (group 2b, p = 1.000) or peracetic acid solution (group 2c, p = 0.352). For Duralay groups, the use of peracetic acid solution did not affect the horizontal dimension of the specimens when T0 was compared to T168 only with water as a storage medium (group 1b, p = 1.000). Additionally, T0 did not differ from T24 for groups 1c (p = 0.553), 2b (p = 1.000), 2d (p = 0.234), and 2e (p = 1.000) and from T48 for groups 1d (p = 0.118) and 2b (p = 1.000). Conclusion Within the studied conditions, the use of 0.2% peracetic acid can be safely used as a disinfectant solution regarding dimensional stability of AR-indexed IFPD until 7 days of storage. Horizontal discrepancies are dependent on acrylic resin type, time, and medium of storage.